Креативний маркетинг у розвитку туристичних дестинацій - Шостак, Віктор Михайлович; Москвич, Ольга Дмитрівна (My University, 2024)
У сучасному світі туризм визнається однією з основних галузей економіки, яка впливає на соціальний та культурний розвиток країн. Тому Україна, як потенційна туристична дестинація, має великий потенціал, але для його реалізації необхідно використовувати ефективні маркетингові стратегії. В цьому контексті маркетинг стає критично важливим інструментом, оскільки від його ефективності залежить успіх країни як туристичної дестинації. Креативний маркетинг відіграє важливу роль у формуванні позитивного іміджу країни, цільової аудиторії та створенні унікальної туристичної пропозиції. Подальший розвиток туризму в умовах війни вимагає комплексного підходу та використання різноманітних стратегій. Стратегічне планування маркетингових заходів передбачає не лише розробку іміджу, спрямованого на приваблення молодого покоління, але й активні заходи, спрямовані на різноманітність туристичного продукту. Крім того, співпраця з міжнародними партнерами та участь у міжнародних заходах можуть значно збільшити привабливість України як туристичної дестинації на світовому ринку

In today's world, tourism is recognized as one of the main sectors of the economy that influences the social and cultural development of countries. Therefore, Ukraine, as a potential tourist destination, has great potential, but to realize it, effective marketing strategies need to be used. In this context, marketing becomes a critical tool, as the country's success as a tourist destination depends on its effectiveness. Creative marketing plays an important role in shaping the country's positive image, target audience, and creating a unique tourism offer. Further development of tourism in times of war requires a comprehensive approach and the use of various strategies. Strategic planning of marketing activities involves not only the development of an image aimed at attracting the younger generation, but also active measures aimed at diversifying the tourism product. In addition, cooperation with international partners and participation in international events can significantly increase the attractiveness of Ukraine as a tourist destination in the global market. However, there are challenges that need to be addressed to achieve the full potential of Ukrainian tourism. Insufficient specification of the tourism product and economic difficulties in some regions require attention and a comprehensive approach to the development of marketing strategies. The use of creative marketing tools aimed at solving these problems can ensure Ukraine's stable and competitive position in the international tourism market. It is emphasized that for the development of Ukraine as a tourist destination, especially in the context of war and post-war recovery, important strategies include the development of interesting and unusual tourist routes, cultural events and festivals, launching advertising campaigns on social media, cooperation with influential bloggers and travelers, and creating unique content to attract attention. It is noted that special attention should be paid to those creative marketing strategies aimed at increasing the environmental and social responsibility of tourist destinations
Keywords: креативний маркетинг; туристичні дестинації; стратегічне планування; маркетингові стратегії; конкурентні переваги; регіональний розвиток; міжнародні партнери; цільова аудиторія; creative marketing; tourist destinations; strategic planning; marketing strategies; competitive advantages; regional development; international partners; target audience